Innovative technologies in the production of electricity through waste processing: International experience and perspectives (Международный научный журнал «Инженер», 2026)
This article reviews modern innovative technologies for generating electricity from waste. Convertingwaste into energy is one of the most effective, innovative and economically viable approaches toachieving environmental sustainability today. Also, the introduction of waste-to-energy technology is notonly a solution to environmental problems, but also a new development factor for the country's economy.Effective methods are analyzed based on international experience and their environmental and economicadvantages are studied. The application of technologies is analyzed using the example of advancedprojects from leading countries in the world.